2013
DOI: 10.1038/ajg.2012.453
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and the Risk for Crohn's Disease and Ulcerative Colitis: Data From a European Prospective Cohort Study (The IBD in EPIC Study)

Abstract: Obesity as measured by BMI is not associated with the development of incident UC or CD. Alternative measures of obesity are required to further investigate the role of obesity in the development of incident IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
147
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(162 citation statements)
references
References 32 publications
7
147
5
Order By: Relevance
“…In a prospective cohort study (EPIC cohort) of European adults, BMI was not associated with a specific phenotype of disease behaviour or disease location (13) as in the our study. This could be explained by the chronic status of CD in patients with stenosis as compared to luminal disease, what could explain the low BMI in this specific phenotype of patients.…”
Section: Figure 1 Visceral Fat Percentiles (Grams) Among Groupssupporting
confidence: 46%
“…In a prospective cohort study (EPIC cohort) of European adults, BMI was not associated with a specific phenotype of disease behaviour or disease location (13) as in the our study. This could be explained by the chronic status of CD in patients with stenosis as compared to luminal disease, what could explain the low BMI in this specific phenotype of patients.…”
Section: Figure 1 Visceral Fat Percentiles (Grams) Among Groupssupporting
confidence: 46%
“…A large prospective study found no association between obesity and development of incident IBD [64]. This cohort had a predominance of middle-aged subjects, the median age being approximately 53 years.…”
Section: The Changing Phenotype Of Ibdmentioning
confidence: 99%
“…4 of 5 published studies [11,33,36,53,59] support this hypothesis in showing an association between regular physical activity and a reduced risk of developing CIBD Klein et al [36] questioned habitual physical activity in recent onset cases (53 UC and 33 CD), finding a low level of activity prior to the development of clinical disease. In 3 421 972 person years of follow-up in the Nurses Health Studies [33], 284 cases of CD and 363 cases of UC were identified.…”
Section: Physical Activity In the Prevention Of Ibdmentioning
confidence: 71%
“…In a second study, patients with medical or psychiatric abnormalities were excluded, and despite similar accelerometer readings, the patients had greater subjective and objective muscle fatigue than controls [67]. A third negative report [11] included more cases with UC than with CD, and diagnostic criteria were not standardized. In the fourth negative study [60], 23 % of those with CD reported greater fatigue, and 21 % noted reduced leisure activities, although a brief interview by the principal investigators had found similar proportions of patients and controls reporting high, moderate or low levels of physical activity Thus, a level of habitual physical activity that is lower than that of controls and below current minimum recommendations for general health is a relatively consistent finding in CIBD.…”
Section: Current Levels Of Habitual Physical Activity In Ibdmentioning
confidence: 99%